Social engagement and allostatic load mediate between adverse childhood experiences and multimorbidity in mid to late adulthood: the Canadian Longitudinal Study on Aging. Issue 4 (23rd March 2023) - Atkinson, Leslie; Joshi, Divya; Raina, Parminder; Griffith, Lauren E.; MacMillan, Harriet; Gonzalez, Andrea
Abstract: Background: Adverse childhood experiences (ACEs) are associated with multimorbidity in adulthood. This link may be mediated by psychosocial and biological factors, but evidence is lacking. The current study evaluates this mediation model. Method: We analyzed data from the Canadian Longitudinal Study of Aging ( N = 27 170 community participants). Participants were 45–85 years at recruitment, when allostatic load and social engagement data were collected, and 3 years older at follow-up, when ACEs and multimorbidity data were collected. Structural equation modeling was used to test for mediation in the overall sample, and in sex- and age-stratified subsamples, all analyses adjusted for concurrent lifestyle confounds. Results: In the overall sample, ACEs were associated with multimorbidity, directly, β = 0.12 (95% confidence interval 0.11–0.13) and indirectly. Regarding indirect associations, ACEs were related to social engagement, β = −0.14 (−0.16 to −0.12) and social engagement was related to multimorbidity, β = −0.10 (−0.12 to −0.08). ACEs were related to allostatic load, β = 0.04 (0.03–0.05) and allostatic load was related to multimorbidity, β = 0.16 (0.15–0.17). The model was significant for males and females and across age cohorts, with qualifications in the oldest stratum (age 75–85). Conclusions: ACEs are related to multimorbidity, directly and via social engagement and allostatic load. This is the first study to show mediated pathways between early adversity and multimorbidity in adulthood. It provides a platform for understanding multimorbidity as a lifespan dynamic informing the co-occurrence of the varied disease processes represented in multimorbidity.